Aplikasi Pre-Heating dan Edible Coating untuk Peningkatan Kualitas Keripik Kentang - Adolf Parhusip; Aileen Neysha; Lincoln Halim; Fernando Ogyen Iwantoro (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2021)
This study aimed to improve the crispness and to reduce oil absorption in potato chips. Potato chips crispness was improved by applying pre-heating, namely boiling and steaming before frying, while oil absorption was reduced by adding acacia gum as an edible coating. Boiling and steaming was conducted at 100°C for 0, 2, 3, 4, 5, and 6 minutes. Acacia gum (0, 3, 4, 5, and 6%) and calcium chloride (0, 0.5, and 1%) were added in the formulation. Boiling for 4 minutes yielded hardness of 384.902±25.10 g, moisture content of 3.02±0.07%, crispness score of 5.04±0.60 (crispy), and overall hedonic score of 5.10±1.43 (somewhat like). Further process by adding acacia gum 5% and calcium chloride 1% yielded potato chips with fat content of 28.01±1.56%, oil absorption ratio of 0.32±0.03, moisture content of 1.07±0.78%, and hardness level of 411.111±25.32 g. The products recuded oil absorption during frying up to 41.81±5.86%.